2011
DOI: 10.1007/s00606-011-0502-7
|View full text |Cite
|
Sign up to set email alerts
|

Prolamin storage proteins and alloploidy in wild populations of the small grass Brachypodium distachyon (L.) P. Beauv.

Abstract: This paper reports the glutenin diversity of a collection of 23 wild populations of the grass Brachypodium distachyon collected in the Mediterranean and southern areas of the Iberian Peninsula. The plant material studied included the three different cytotypes of this species: 2n = 10, 2n = 20 and 2n = 30. A specific method of extraction was used to isolate the glutenin subunits from the caryopsis. Separation by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) showed them to correspond to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
2
10
0
1
Order By: Relevance
“…For instance, genotype Bs115 is more related with three genotypes of B. distachyon than the other three genotypes of B. stacei, Moreover, Bd160 and Bh486, appear clearly separated on the dendrogram, probably due to these genotypes have, respectively, the shortest and the largest radicular system of the genotypes of B. distachyon and B. hybridum analysed. These results are similar to those obtained by other authors using biochemical and molecular markers to differentiate between the members of a large collection of genotypes belonging to the present three species of Brachypodium (including those studied in the present work) (Hammami et al 2011(Hammami et al , 2014. The overlap observed in the grouping of the genotypes of the three species can be explained by the existing evolutionary proximity among them, being B. hybridum an allotetraploid of the other two species.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, genotype Bs115 is more related with three genotypes of B. distachyon than the other three genotypes of B. stacei, Moreover, Bd160 and Bh486, appear clearly separated on the dendrogram, probably due to these genotypes have, respectively, the shortest and the largest radicular system of the genotypes of B. distachyon and B. hybridum analysed. These results are similar to those obtained by other authors using biochemical and molecular markers to differentiate between the members of a large collection of genotypes belonging to the present three species of Brachypodium (including those studied in the present work) (Hammami et al 2011(Hammami et al , 2014. The overlap observed in the grouping of the genotypes of the three species can be explained by the existing evolutionary proximity among them, being B. hybridum an allotetraploid of the other two species.…”
Section: Discussionsupporting
confidence: 92%
“…The plant materials examined included four genotypes each of B. distachyon (2n = 10) (including genotype Bd-21, the full genome of which has been sequenced by the Interna- These genotypes all originated from single plants belonging to 11 wild populations (three of B. dystachyon and four each of B. stacei and B. hybridum), harvested in different places around the Iberian Peninsula (Hammami et al 2011) (Table S1*).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The allopolyploid origin of B. hybridum is currently out of debate mainly based upon the strong cytogenetic evidences reported by Hasterok and co-workers (Hasterok et al 2004(Hasterok et al , 2006Idziak et al 2011). It has also been confirmed by the analysis of plastid and nuclear gene sequences (Catalán et al 2012) and prolamin storage protein profiles (Hammami et al 2011) on collections of B. distachyon (s.l.) including samples representative of the three cytotypes.…”
Section: Resultsmentioning
confidence: 94%
“…Phylogenetic analyses of two plastid (ndhF and trnLF) and five nuclear (ITS, ETS, CAL, GI, and DGAT) genes indicated that the more early-diverging B. stacei and the more recently evolved B. distachyon emerged from two independent lineages, confirming their contributions as genome donors to B. hybridum (Catalán & al., , 2014. Further evidence from different molecular sources, like seed protein data (Hammami & al., 2011), nuclear SSRs (Giraldo & al., 2012), DNA barcoding , and isozymes (Jaaska, 2014) have also confirmed the co-occurrence of progenitor B. distachyon and B. stacei markers in the B. hybridum background.…”
Section: Introductionmentioning
confidence: 99%